Volta Drive Connect: Science Kit to Stimulate the Elementary Students in Sustainable Development - Rahmania, Khaerini; Saniyyah, Farah Nailis; Afina, Firnanda Millatin; Hanifah, Desty Putri (Universitas Muhammadiyah Purworejo, 2024)
The goal of this research is to develop the Volta Drive Connect science kit to increase energy literacy and inspire students to play a role in sustainable development. Volta Drive Connect consists of three levels with different components and levels of assembly difficulty. The research methodology uses developmental research with the ADDIE model (Analysis, Design, Development, Implementation, and eval__uation). The analysis phase involves the identification of learning needs and student characteristics. Instruments used are performance rubrics, observations, interviews, and documentation. The eval__uation of the effectiveness of the teaching kit was carried out using a paired samples test comparing student learning outcomes before and after using Volta Drive Connect. The test results show a significance value of 0.000 (p < 0.05), indicating a significant difference between the pre-test and post-test. Students' energy literacy increased significantly between before and after implementing Volta Drive Connect. Qualitative analysis of observation and interview data revealed increased learning motivation and student engagement during the use of the kit. Minor technical challenges identified during implementation were noted for improvement in future iterations of the kit. The development of Volta Drive Connect was successful in creating a learning medium that is effective in increasing energy literacy, and aligned with the goals of the SDGs.